Old Iron Age – Middle Iron Age Cemetery in Vilkija, According to the Data of the Archaeological Research Conducted in 2016 and 2023 - Račas, Justinas; Vasiliauskas, Liudvikas; Baubonis, Zenonas (Archaeologia Lituana, 2024)
An article is discussed Old – Middle Iron Age burial ground in Vilkija (Kaunas district), excavated in 2016 and 2023. Objective was to gather fragmented information and finds from this period from museums and other sources. As well there were made radioactive carbon (14C) analysis of burials and X-ray Fluorescence (XRF) analysis of finds.
Keywords: Old Iron Age; Middle Iron Age; burial ground